Bioprocess engineering an introductory engineering and life science approach - Clarke, Kim Gail (Woodhead Publishing, 2013)
This book details the application of chemical engineering principles for the development, design, operation and scale up of bioprocesses.
Available through Woodhead Publishing Online.
Includes index.
Keywords: Engineering.; Biochemical engineering.; Biotechnology.; elektronické knihy; electronic books